Symptoms trend and challenges in dental practice during delta variance COVID-19 pandemic in Indonesia: Google Trends Analysis [version 2; peer review: 2 approved] - Faizul Hasan; Noor Rohmah Mayasari; Eisner Salamanca; Hendrik Setia Budi; Kamaluddin Latief; Mokh. Sujarwadi; Odontuya Dorj; Rahmat Dani Satria (F1000Research, 2023)
Background: The COVID-19 pandemic has grown to be a serious issue on a global scale. Dental care is one of the industries affected by COVID-19. The surveillance utilizing lifetime data, however, is still not clear. The purpose of this study was to use Google Trends (GT) analysis to examine symptom trends and challenges during the COVID-19 outbreak in Indonesia. Methods: Covid-19 cases retrieve from Our World in Data. The cases were collected between 1 April 2021-30 September 2021. The GT was used to discover Indonesian relative search volume (RSVs) covering the timeframe of the first outbreak covid-19 pandemic in Indonesia on 1 March 2020 until 13 February 2022. The duration of the search was chosen to reflect the relative popularity of the keywords "symptoms and dentistry practice challenge-related terms" and "coronavirus". Results: We observed that there was a significant and positive correlation between the COVID-19 daily case using GT RSV data and the COVID-19 case from Our World in Data. The COVID-19 daily case had a strong correlation with search terms related to symptoms (such as fever, sore throat, flu, toothache, and cough), drugs (such as ibuprofen, paracetamol, demacolin, bodrex, and antibiotic), and health management (such as self-isolation and telemedicine). Conclusion: Using GT may be helpful to observe the current symptoms trends as well as its challenge tendencies as a surveillance tool for a continuing pandemic like COVID-19. GT should be considered and used as it has the potential to be a powerful digital epidemiology tool that can provide more insight into disease dynamics.